2018 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2018
DOI: 10.1109/pesgm.2018.8586256
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Reactive Power for Voltage Control in Lossy Networks

Abstract: Reactive power has been proposed as a method of voltage control for distribution networks, providing a means of increasing the amount of energy transferred from distributed generators to the bulk transmission network. The value of reactive power can therefore be measured according to an increase in transferred energy, where the transferred energy is defined as the total generated energy, less the total network losses. If network losses are ignored, an error in the valuation of a given amount of reactive power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The combination of the analytic (Two‐Bus) approach with detailed simulations shows similarities with [10–12]. The authors of [12] highlight reasons as to why certain DG generation profiles lead to a greater curvature in the total losses with DG penetration (i.e., a narrower ‘U‐shaped curve'), whilst the authors of [10] present analytic arguments to propose improved settings for inverter controls.…”
Section: Case Studiesmentioning
confidence: 95%
See 3 more Smart Citations
“…The combination of the analytic (Two‐Bus) approach with detailed simulations shows similarities with [10–12]. The authors of [12] highlight reasons as to why certain DG generation profiles lead to a greater curvature in the total losses with DG penetration (i.e., a narrower ‘U‐shaped curve'), whilst the authors of [10] present analytic arguments to propose improved settings for inverter controls.…”
Section: Case Studiesmentioning
confidence: 95%
“…For example, we have shown that network voltage drop has a huge effect on relative losses when using voltage control, and we have also clearly demonstrated the existence of non‐trivial bounds on the VCLF. To our knowledge, these points have not been explored in prior works, with the exception of related analytic results we first presented in [11] for the related (but distinct) valuation error metric. Here we present a wider range of analysis (e.g., considering PQ$ PQ$ and PV$ PV$ control), and provide detailed simulations that were missing in that earlier paper—the simulations in this work have enabled the validation of the approach comprehensively.…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations